Efficiency and farm size in Philippine aquaculture - Analysis in a ray production frontier framework - Irz, Xavier; Stevenson, James R. (Firenze University Press, 2012)
We investigate the existence of an inverse relationship (IR) between farm size and technical efficiency in Philippine brackishwater pond aquaculture. The study is motivated by the exemption of fish ponds from the Comprehensive Agrarian Reform Laws and suggestions in the literature of inefficient management of fish farms. The analysis of technical efficiency is based on the estimation of a multi-product ray production function estimated in a stochastic frontier framework. There is some evidence of an IR but of only limited strength. Hence, it is unlikely that agrarian reform is the key to unlocking the productive potential of brackishwater aquaculture in the Philippines.
Keywords: Ma; rausku; Filippiinit; vesiviljely; maareformi; tehokkuus; aquaculture; Philippines; efficiency; land reform; rays; inverse relationship; ray production function